The effects of remote ischaemic preconditioning on coronary artery function in patients with stable coronary artery disease. (1st February 2018) - Corcoran, D.; Young, R.; Cialdella, P.; McCartney, P.; Bajrangee, A.; Hennigan, B.; Collison, D.; Carrick, D.; Shaukat, A.; Good, R.; Watkins, S.; McEntegart, M.; et al.
Abstract: Background: Remote ischaemic preconditioning (RIPC) is a cardioprotective intervention invoking intermittent periods of ischaemia in a tissue or organ remote from the heart. The mechanisms of this effect are incompletely understood. We hypothesised that RIPC might enhance coronary vasodilatation by an endothelium-dependent mechanism. Methods: We performed a prospective, randomised, sham-controlled, blinded clinical trial. Patients with stable coronary artery disease (CAD) undergoing elective invasive management were prospectively enrolled, and randomised to RIPC or sham (1:1) prior to angiography. Endothelial-dependent vasodilator function was assessed in a non-target coronary artery with intracoronary infusion of incremental acetylcholine doses (10 − 6, 10 − 5, 10 − 4  mol/l). Venous blood was sampled pre- and post-RIPC or sham, and analysed for circulating markers of endothelial function. Coronary luminal diameter was assessed by quantitative coronary angiography. The primary outcome was the between-group difference in the mean percentage change in coronary luminal diameter following the maximal acetylcholine dose (Clinicaltrials.gov identifier:NCT02666235 ). Results: 75 patients were enrolled. Following angiography, 60 patients (mean ± SD age 57.5 ± 8.5 years; 80% male) were eligible and completed the protocol (n = 30 RIPC, n = 30 sham). The mean percentage change in coronary luminal diameter was − 13.3 ± 22.3% and − 2.0 ± 17.2% in the sham and RIPC groups respectively (difference 11.32%, 95%CI: 1.2– 21.4, p = 0.032). This remained significant when age and sex were included as covariates (difference 11.01%, 95%CI: 1.01– 21.0, p = 0.035). There were no between-group differences in endothelial-independent vasodilation, ECG parameters or circulating markers of endothelial function. Conclusions: RIPC attenuates the extent of vasoconstriction induced by intracoronary acetylcholine infusion. This endothelium-dependent mechanism may contribute to the cardioprotective effects of RIPC.